Intermediando o risco: novos formatos institucionais na difusão das ferramentas da indústria de capital de risco nos bancos públicos do Brasil - Cavenaghi, Felipe (2017)
The project chased the characterization of the new institutional formats in the diffusion of the logic of venture capital in the public banks of Brazil, as public banks are adopting tools linked to the venture capital industry with the justification of gaining greater financial flexibility, otherwise the agents would use these structures legitimized in the financial market with the purpose of seeking greater innovation leveraging the development of the economy. The collection of data was done through financial reports as well as normative reports. In the analysis the adopted structures and the interactions with the other agents of the financial space were identified with the proposal of an analysis framework taking into account the economic sociology and the theory of the organizations.